ANALYSIS RESULTS JUDGING WORLD CHAMPIONSHIPS IN MEN'S ARTISTIC GYMNASTICS IN THE LONDON 2009 YEAR - Snežana Bijelić; Nađija Avdibašić Vukadinović1; Sunčica Delaš Kalinski; Almir Atiković (University of Banja Luka, Faculty of physical education and sport, 2011)
On a sample of 176 male gymnasts, we analyzed the score of judges from the World Championship in men's artistic gymnastics, held 2009 in London. The subject of the analysis was the final scores competitors got for the exercises shown in the qualifying competition (C I). Analysis problem was determination of the differences on individual apparatus between judges E1 to E6 and apparatus. The main objective of this study was to determine the reliability of evaluation of judges and whether the current Code of Points (Federation Internationale de Gymnastique, 2009b) should be revised in terms of equalizing score on apparatus. Equality was tested for the achieved D, E and all-around scores on the disciplines of floor exercise, pommel horse, rings, vault, parallel bars and horizontal bar. Vault has the highest D and E scores, while pommel horse the lowest D and E scores. T-tests showed that those two disciplines significantly differ from other disciplines. Reliability were calculated (intraclass correlation coefficient ICR, Cronbach's alpha, differences in mean E1 to E6 between judges were tested using factor analyses with method first major component. All data was analyzed using SPSS Statistics 17.0. Results show very high reliability (e.g. Cronbach's alpha range from .94 up to .98).